Rahab the harlot in Severian of Gabala"s De paenitentia et compunctione (de Rahab historia): Paradox, anti-Judaism and the early Christian invention of the penitent prostitute - De Wet, Chris L. (HTS teologiese studies, 2020)
This article examines the 4th-century CE interpretation of the story of Rahab the Harlot by Severian of Gabala, in his homily, De paenitentia et compunctione (CPG 4186). In this article, a close and critical reading of Severian’s references to the story of Rahab in De paenitentia et compunctione (with some comparative reference to other works of Severian, and also of John Chrysostom and Pseudo-Chrysostom) is provided. It is asked, ‘how and why could a treacherous harlot, a prostitute, who was considered to be the epitome of vice in early Christian moral deliberations, function as an exemplum for Severian?’ The article firstly asks how Severian deals with the problematic and paradoxical aspects of Rahab, namely, the fact that she was a prostitute and also a liar. Then, it illustrates how Severian transforms Rahab into a Christian heroine and how he deploys these qualities of the transformed Rahab in a potent anti-Judaistic rhetoric. This study is finally concluded with a somewhat broader delineation of the importance of Rahab in the development of a curious Christian cultural and moral trope, namely, the penitent prostitute. Such a study of Rahab is significant not only in that it expands our understanding of the history of women and gender dynamics in early Christianity, but it also elucidates the complex and strategic discursive moves employed by male Christian authors to deal with the seemingly ‘bad girls’ of scripture.Contribution: This article investigates the historical reception of the story of Rahab (Jos 2) in a little-known homily by Severian of Gabala. The focus is how Severian interprets the story and the paradoxical figure that is Rahab, with reference to its use as an anti-Judaistic trope, and its role in the shaping of the cultural phenomenon that is the penitent prostitute in early Christian thought.